1993
DOI: 10.1111/j.2042-7158.1993.tb03706.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrhoeic activity of quercitrin in mice and rats

Abstract: Quercitrin, a flavonoid isolated from Euphorbia hirta, shows antidiarrhoeic activity at doses of 50 mg kg-1, against castor oil- and PGE2-induced diarrhoea in mice, but not when magnesium sulphate is used as a cathartic agent. It also delays rat small intestinal transit if this is accelerated with castor oil. However, the flavonoid does not modify the fluid transport across the colonic mucosa when it is administered intraluminally, either in normal conditions or when this transport is altered by PGE2 or sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 17 publications
(11 reference statements)
4
57
0
2
Order By: Relevance
“…Magnesium sulphate causes increased loss of intestinal content due to the reduction in reabsorption of water and cholecystokinin release from the duodenal mucosa. These increase the secretion and motility of small intestine, prevent the reabsorption of sodium chloride and water, and induce diarrhea (Gálvez et al, 1993;Uddin et al, 2005). In this study, the extracts showed a dose-dependent reduction in fecal droppings in both castor oil-and magnesium sulphate-induced diarrhea (Table 2).…”
Section: Discussionmentioning
confidence: 52%
“…Magnesium sulphate causes increased loss of intestinal content due to the reduction in reabsorption of water and cholecystokinin release from the duodenal mucosa. These increase the secretion and motility of small intestine, prevent the reabsorption of sodium chloride and water, and induce diarrhea (Gálvez et al, 1993;Uddin et al, 2005). In this study, the extracts showed a dose-dependent reduction in fecal droppings in both castor oil-and magnesium sulphate-induced diarrhea (Table 2).…”
Section: Discussionmentioning
confidence: 52%
“…In a previous study it was demonstrated that quercitrin had antidiarrhoeic activity in several models of experimental diarrhoea in mice (Galvez et al, 1993b). In that study, the effects of quercitrin on small intestine transit as well as on fluid transport across the colonic mucosa in rats were also evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we demonstrated that quercitrin showed antidiarrhoeic activity in mice and rats (Galvez et al, 1993a;Galvez et al, 1993b), from doses of 25 mg/kg, in several models of experimentally-induced diarrhoea.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Five extracts were potential antioxidants: C. dioscoridis, Solanum nigrum, Salvia lanigera, O. syriacum 6 , and Solenostemma arghel 10 . Both C. dioscoridis and E. hirta extracts showed antidiarrheal 11,12 , hypoglycemic 13,14 , and antimicrobial activities 15,16 . In addition, Salvia lanigera aerial parts ether soluble fraction was found to be highly effective against Gram-positive bacteria (Sreptomyces viridochromogenes) 17 .…”
Section: Introductionmentioning
confidence: 99%